2018
DOI: 10.7180/kmj.2018.33.1.85
|View full text |Cite
|
Sign up to set email alerts
|

IgA nephropathy in a patient with ankylosing spondylitis well controlled with etanercept

Abstract: Ankylosing spondylitis (AS) can involve the eye, gastrointestinal system, cardiopulmonary system, skin, kidneys, and spinal and peripheral joints. It is rarely accompanied by immunoglobulin A (IgA) nephropathy. Although IgA is involved in both AS and IgA nephropathy, the relationship between these diseases remains unclear. We detected hematuria and proteinuria in a 32-year-old male patient with ankylosing spondylitis that remained stable for 4 years through treatment with etanercept, a tumor necrosis factor-α … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…1,8 Some studies have reported clinical cases in which the development of IgA nephropathy seems to be associated with the use of TNFi. 4,[9][10][11][12] In fact, 3 previous cases reported IgA nephropathy in AS patients treated with infliximab or etanercept. [10][11][12] Our case is the first report with an AS patient treated with adalimumab who develop IgA nephropathy and in whom it was necessary to discontinue the TNFi.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,8 Some studies have reported clinical cases in which the development of IgA nephropathy seems to be associated with the use of TNFi. 4,[9][10][11][12] In fact, 3 previous cases reported IgA nephropathy in AS patients treated with infliximab or etanercept. [10][11][12] Our case is the first report with an AS patient treated with adalimumab who develop IgA nephropathy and in whom it was necessary to discontinue the TNFi.…”
Section: Discussionmentioning
confidence: 99%
“…4,[9][10][11][12] In fact, 3 previous cases reported IgA nephropathy in AS patients treated with infliximab or etanercept. [10][11][12] Our case is the first report with an AS patient treated with adalimumab who develop IgA nephropathy and in whom it was necessary to discontinue the TNFi. Despite, other studies have already reported IgA nephropathy associated with adalimumab, but in patients with other immunologic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation